Practical web scraping for data science : best practices and examples with Python - Broucke, Seppe vanden, 1986-; Baesens, Bart (Apress, 2018)
Includes many larger, fully worked out examples, this book provides a complete and modern guide to web scraping, using Python as the programming language, without glossing over important details or best practices. --